A meta-analytical study of the antecedents of customer engagement - Kaur, Jaspreet; Anbumathi, R.; Bhat, Vidya; Chhabra, Sheetal; Tandulwadkar, Rucha; Srivastava, Shalini; Aggarwal, Shreya (International journal of economic perspectives, 2025)
This study fills a gap in customer engagement (CE) literature by exploring the influence of emotions and psychological differences. It analyses the relationship between nine antecedents—brand experience, consumer age, trust in brand, involvement, customer satisfaction, interaction, reward, perceived value, and product quality—and five CE outcomes: word of mouth, loyalty, brand commitment, purchase intention, and firm performance. A meta-analysis of 101 studies identifies 14 antecedents of CE, considering moderators such as sample size, publication year, study context (product vs. services), and location. Results indicate moderate to high effect sizes for all antecedents on CE, with significant impacts from the moderators. The study provides theoretical and managerial implications based on these findings.